Normative Ethics and Descriptive Ethics Concerning the Context of Politeness in the ondhagga Tradition in Madura - Mudhar; Makinuddin; Simanjuntak, Nensy Megawati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Language and ethics are intrinsically linked, with ethics playing a crucial role in ensuring politeness and recognizing social distinctions among speakers. One regional language rich in ethical traditions is Madurese, particularly through a practice known as ondhagga. This tradition emphasizes the importance of speech and grammar tailored to the social position of the person being addressed. In Madurese culture, the speaker must consider the listener's social status to appropriately use ondhagga forms. This research highlights two types of ethics within this tradition: normative and descriptive ethics. Normative ethics focuses on defining the behaviors and values that are considered morally good within a social group, guiding individuals on appropriate actions without making judgments. On the other hand, descriptive ethics describes existing behaviors and their meanings, offering insight into actions without prescribing standards. The study analyzed twenty conversational samples across various contexts using qualitative, phenomenological methods. Data was collected through documentation, and analysis was conducted using data reduction and presentation techniques. To ensure validity, the research employed data triangulation and credibility testing. The aim was to explain how normative and descriptive ethics operate within the ondhagga tradition. The findings emphasize the importance of ethical communication, tailored to context and situation. It underscores that ethics in a language not only applies to Madurese but is relevant across all languages and cultures. Ultimately, language ethics reflects our nobility as human beings, as it shapes respectful communication in everyday interactions.